Karakteristik Morfogenetik Ayam Kokok Balenggek Di Kecamatan Tigo Lurah Kabupaten Solok - Firda Arlina; Dasmi Ahmad; Tinda Afriani; Lany Madina (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2007)
The study was aimed to define the morphogenetic characteristics of native song fowl chickens of West Sumatra called Kokok Balenggek. Sixty Kokok Balenggek chickens raised by farmers in Tigo Lurah sub district, Solok district were used as samples. They consisted of 40 males and 20 females. Both qualitative and quantitative morphogenetic data were collected and measured, including: color of feather and shank; form of comb; length of tars metatarsus, tibia, femur; body weight and distance between pelvis bone by females. By males, feather color of Kokok Balenggek chickens were dominated by wild feather type (e+) and silver (S) of 42,5 % and 22,5 %, respectively. Comb were mostly single form (90 %). While feather color of females were dominated by black (S) and white (25 % each), pea comb (90 %), shank color of white yellow (Id) (85 %). Length of metatarsus for male and females of 100,2 + 11,05 mm, 80,03 + 8,64 mm; tibia of 134,40 + 18,73 and 117,14 + 10,24 mm; femur of 103,36 + 16,94 and 85,63 + 11,47 mm; body weight of 1,74 + 0,46 kg and 1,1 + 0,62 kg/head, respectively. Data of distance length between pelvis bone by females were found 41,17 + 4,32 mm.